114 Hypothermia is preventable. (11th October 2021) - Collins, L; Wood, J; Faire, A; Kakade, G; Barrett, S; Patel, F; Panjwani, Deepa; Rao, S
Abstract : Background: Temperature regulation is an important part of new-born care. This is especially true of pre-term infant and those with the low-birth weight, which represent a significant proportion of the population in the neonatal unit. Aim: The audit was performed to assess the quality of care in relation of hypothermia. The audit was aimed at observing babies admitted to neonatal unit Leicester Royal Infirmary and Leicester General during the months of June -July (period 1) and November – December (period 2), with a body temperature below the 36.5. The second objective was to look at the documentation of the admission temperature Methods: The data was collected retrospectively. Babies were identify using the online record system. Data was also collected on gestational age, birth weight, reason for admission and duration of stay. The data was recorded and analysed using Microsoft Excel and kept anonymous. After the first review, we applied the teaching sessions for the labour staff/midwives and also introduced the flyer/poster was displayed in theatres, postnatal wards, labour wards. Email sent to all staff at LGH and LRI Maternity units Results. There were 119 admissions between period 1 and 124 admissions between period 2. Temperature recordings within 30 minutes of admission to the Neonatal Unit was measured and documented for babies in first period as 99% and 100% in second period. 100% achievement of admission target temperatures between 36.5 – 37.50C were recorded as 81% and 86% for respective periods. There were 24 and 21 patients who had temperatures outside the limit. The majority of patients had temperature >36.5 as they have been admitted for sepsis treatment. Babies with hypothermia were >33 and <37 weeks gestational in 42% and 44% in reviews. 50% of babies were above 2.5 kg in period 2. For both periods, babies admitted with a temperature lower than 36.5 were treated for sepsis and they were admitted from labour ward and theatre. Conclusion: An excellent level of documentation compliance was observed. With minimum intervention, normothermic admissions improved to 5%. There still remains room for improvement in areas to prevent hypothermia. The particular at-risk age group appears to be between 33-37 weeks and weight above 2.5 kg.